Effect of intravenous transplantation of bone marrow mesenchymal stem cells on neurotransmitters and synapsins in rats with spinal cord injury - Chen, Shaoqiang (Neural Regen Res, 2012)
Bone marrow mesenchymal stem cells were isolated, purified and cultured in vitro by Percoll density gradient centrifugation combined with the cell adherence method. Passages 3–5 bone marrow mesenchymal stem cells were transplanted into rats with traumatic spinal cord injury via the caudal vein. Basso-Beattie-Bresnahan scores indicate that neurological function of experimental rats was significantly improved over transplantation time (1–5 weeks). Expressions of choline acetyltransferase, glutamic acid decarboxylase and synapsins in the damaged spinal cord of rats was significantly increased after transplantation, determined by immunofluorescence staining and laser confocal scanning microscopy. Bone marrow mesenchymal stem cells that had migrated into the damaged area of rats in the experimental group began to express choline acetyltransferase, glutamic acid decarboxylase and synapsins, 3 weeks after transplantation. The Basso-Beattie- Bresnahan scores positively correlated with expression of choline acetyltransferase and synapsins. Experimental findings indicate that intravenously transplanted bone marrow mesenchymal stem cells traverse into the damaged spinal cord of rats, promote expression of choline acetyltransferase, glutamic acid decarboxylase and synapsins, and improve nerve function in rats with spinal cord injury.